Persepsi Maskulinitas Terhadap Loyalitas Merek Rokok Surya di Kota Kudus - Zuyyin Choiriyyatun Felasuf; Ira Mutianing Sari; Ruth Natalia Susanti (PT PUSTAKA CENDEKIA GROUP, 2025)
This study aims to determine the role of perceived masculinity in shaping loyalty to the Surya cigarette brand among men aged 20–30 in Kudus City. A descriptive quantitative approach was used, with 20 respondents, active Surya cigarette users who had smoked for at least three years, participating. Data collection was conducted using a five-point Likert scale questionnaire measuring two main variables: perceived masculinity and brand loyalty. The analysis showed an average score of 4.045 for perceived masculinity and 4.24 for brand loyalty. These findings suggest that the masculine image associated with the Surya brand plays a significant role in shaping emotional attachment and consumer loyalty. Theoretically, the results support the view of modern consumer psychology, which states that consumption behavior is driven not only by functional needs but also by social and symbolic meanings that shape self-identity. Thus, loyalty to the Surya brand is a form of symbolic consumption that reflects masculine values ​​and the need for social recognition among young men in Kudus.